Direct Electrospinning of Cellulose–Chitosan Composite Nanofiber. Issue 10 (7th May 2013) - Devarayan, Kesavan; Hanaoka, Hirokatsu; Hachisu, Masakazu; Araki, Jun; Ohguchi, Masakatsu; Behera, Bijoya Kumar; Ohkawa, Kousaku
Abstract The direct electrospinning of a non‐derivatized cellulose (Cs)–chitosan (Ch) composite nanofiber is described for the first time. Either of two cellulose preparations from different sources, i.e., cotton (CsC) or bamboo (CsB), is fabricated into composite electrospun non‐woven fabrics (ESNWs) with Ch using the trifluoroacetic acid–acetic acid mixed solvent. The total concentration of Cs + Ch in the mixed solvent is fixed at 4.0 wt.‐% with various Cs/Ch weight ratios of 8:2, 5:5 (Figure shows CsB/Ch‐ESNW), and 2:8, which are fabricated into fine fibers in the Cs/Ch‐ESNWs having average diameters mostly <100 nm. The treatment of the composite fibers with an alkaline–alcohol solution produces the water‐resistant ESNWs, which can retain their fine fibrous network in aqueous environments.<inline-graphic xlink:href="ark:/27927/pgg3j5r6jfc" content-type="mame201200337-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />